2018
DOI: 10.1093/ejo/cjy025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of orthodontic treatment and different fluoride regimens on numbers of cariogenic bacteria and caries risk: a randomized controlled trial

Abstract: The trial was not registered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 25 publications
1
22
0
1
Order By: Relevance
“…Especially the professional application of 12,300 ppm F foam (1.23% acidulated phosphate fluoride (APF)) or varnish in combination with a high fluoride toothpaste (5,000 ppm F) has proven to be the most effective modality (Table 4 ). This confirms that the sole application of fluoride toothpaste (1,450 ppm F) is not sufficient to prevent enamel demineralization [ 69 , 70 ]. Nevertheless, the results from Table 4 should be viewed with caution since the available evidence remains limited.…”
Section: Discussionmentioning
confidence: 59%
“…Especially the professional application of 12,300 ppm F foam (1.23% acidulated phosphate fluoride (APF)) or varnish in combination with a high fluoride toothpaste (5,000 ppm F) has proven to be the most effective modality (Table 4 ). This confirms that the sole application of fluoride toothpaste (1,450 ppm F) is not sufficient to prevent enamel demineralization [ 69 , 70 ]. Nevertheless, the results from Table 4 should be viewed with caution since the available evidence remains limited.…”
Section: Discussionmentioning
confidence: 59%
“…In this study, patients did not pay attention to the kind of toothpaste used, because nearly half of the participants did not know which type of toothpaste they used, and only 37.2% of subjects reported using toothpaste with fluoride. Fluoride toothpaste is recommended to orthodontic patients due to its potential to decrease the risk of the development of caries, especially when a different fluoride regime of toothpastes (1450 ppm and 5000 ppm) is combined [42]. Findings from other studies revealed a higher usage of toothpaste with fluoride, varying from 61% to 81.9% [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Also, a decrease in the high caries risk profile due to increasing the actual chance of avoiding caries in the Cariogram pie chart, using 1,450 ppm fluoride toothpaste was confirmed in the Karabekiroglu et al 16 study, who used Cariogram to evaluate the effectiveness of 1,450 ppm fluoride toothpaste, fluoride varnish and chlorhexidine in adolescents for 12 weeks, and found no significant differences between the mentioned preventive methods. Likewise, Enerback et al 24 recommended the everyday use of high-fluoride toothpaste (5,000 ppm F) or mouth rinse (0.2% NaF), in combination with ordinary toothpaste, to reduce risk of caries during orthodontic treatment. However, saliva secretion and buffer capacity, which are two parameters in the Cariogram, were excluded from their study, due to time restraints and patient convenience - while all parameters of the Cariogram program were analyzed in the present study.…”
Section: Discussionmentioning
confidence: 99%